SIRIM/JICA Seminar on Foundry Technology Development : Casting, Design, Pattern Making and Inspection, 21 July 1992, Shah Alam : [proceedings] - SIRIM/JICA Seminar on Foundry Technology Development : Casting, Design, Pattern Making and Inspection (4th : 1992 : Shah Alam); SIRIM (Shah Alam : SIRIM, 1992)
22